Profile of Students' Problem Solving Ability in Solving Contextual Problems Viewed from Productive Struggle - Syifa Ananda Mefiana; Tatang Herman; Aan Hasanah; Christina Monika Samosir; Rini Melani (STKIP Singkawang, 2024)
Problem solving ability is the ability that allows students to use understanding and facts to solve math problems. Productive struggle is the attitude shown by students when overcoming the difficulties they experience. This study aims to investigate and analyze problem solving ability based on students' productive struggle in solving contextual problems. The research method used is a qualitative approach with data collection techniques through problem solving ability tests, questionnaires regarding productive struggle, and interviews. The research subjects consisted of VIII grade students in several junior high schools. Data analysis was conducted by detailing test results, examining questionnaire responses, and analyzing interviews. The subjects were collected and selected based on the categories of high, medium and low productive struggle. This shows that the problem-solving ability of subjects with high productive struggle is very good, while subjects with medium and low struggle have not shown good things in problem solving ability. This is due to how to overcome the difficulties experienced by students.